Challenges and opportunities for Multi-National Investigator-Initiated clinical trials for ALS: European and United States collaborations. Issue 5 (3rd July 2021) - Lingor, Paul; Koch, Jan C.; Statland, Jeffrey M.; Hussain, Sumaira; Hennecke, Christiane; Wuu, Joanne; Langbein, Thomas; Ahmed, Raees; Günther, René; Ilse, Benjamin; Kassubek, Jan; Kollewe, Katja; et al.
Abstract: An inherent challenge to clinical trials that aim to test the efficacy of experimental therapeutics for patients with amyotrophic lateral sclerosis (ALS) is the relative rarity of the disease. A promising solution to this problem is a multi-center approach that ideally includes sites distributed across a broad geographic area. In support of such an approach, the European E-RARE program and the United States National Institutes of Health (NIH) partnered to support the investigator-initiated ROCK-ALS trial (Eudra-CT-Nr.: 2017-003676-31, NCT03792490) as a multi-national collaboration between centers in Europe and North America that is led by European investigators. During the set-up of this international trial, however, a number of unanticipated legal, administrative, and financial complexities emerged that required significant adaptation of the proposed trial scheme. Here, we report our experience navigating these obstacles and describe the potential solutions that we explored. Our experience may inform future efforts to implement multi-national investigator-initiated trials that involve both European and United States centers.